(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2017)
The present study focused on the influence of different extraction conditions of pectin isolated from ripe mango peel of four Bangladeshi mango varieties (Amrapali, Fazlee, Langra & Kharsapat). The correlation between biochemical properties and protein content were also observed. Five different extraction conditions were applied where the optimum conditions for highest yield and purity were H2SO4-(NH4)2SO4 buffer /pH 1.5 /80 °C /1h /Amrapali and Tem. 99.8 °C/ HCl-NaOH buffer/ pH1.5/ 1h/ Amrapali respectively. The best source among four varieties was Langra as it contained highest purity (AUA, 72.27±0.03%) under a specific condition. The best extractant was HCl-NaOH buffer as the pectin extracting with it contained minimum impurity (3.10±0.06). This study also showed that pectin from Amrapali contained both Low and High Methoxyl pectin with the same extraction condition other than extractant. The proximate, elementary, microbiological, spectroscopical and structural investigations were also conducted in this study. Bangladesh J. Sci. Ind. Res. 52(3), 229-238, 2017